Operational demonstration and process evaluation of non-pneumatic anti-shock garment (NASG) introduction to the public health system of Northern Province, Zambia - Naomi Medina-Jaudes; Andy E. Carmone; Margaret L. Prust; Lupenshyo Ngosa; Oluwaseun Aladesanmi; Morrison Zulu; Andrew Storey; Beauty Muntanga; Caren Chizuni; Angel Mwiche; Hilda Shakwelele; Aniset Kamanga (BMC, 2023)
Abstract Background A disproportionate burden of maternal deaths occurs in low- and middle-income countries (LMICs), and obstetric hemorrhage (OH) is a leading cause of excess mortality. In Zambia, most of maternal deaths are directly caused by OH. The Non-Pneumatic Anti-Shock Garment (NASG) is a first aid tool that uses compression to the abdomen and lower body to stop and reverse hypovolemic shock secondary to OH. We describe the process and experiences introducing the NASG into the Zambia public health system to encourage the development of national policies, clinical guidelines, and implementation plans that feature the NASG. Methods We conducted an observational study of NASG introduction to 143 public health facilities in Northern Province, Zambia, organizing observations into the five dimensions of the RE-AIM evaluation framework: reach, effectiveness, adoption, implementation, and maintenance. The NASG was introduced in August 2019, and the introduction was evaluated for 18 months. Data on healthcare worker training and mentorship, cases where NASG was used, and NASG availability and use during the study period were collected and analyzed. Results The NASG was successfully introduced and integrated into the Zambia public health system, and appropriately used by healthcare workers when responding to cases of OH. Sixteen months after NASG introduction, NASGs were available and functional at 99% of study sites and 88% reported ever using a NASG. Of the 68 cases of recorded OH where a NASG was applied, 66 were confirmed as clinically appropriate, and among cases where shock index (SI) could be calculated, 59% had SI ≥ 0.9. Feedback from healthcare providers revealed that 97% thought introducing the NASG was a good decision, and 92% felt confident in their ability to apply the NASG after initial training. The RE-AIM average for this study was 0.65, suggesting a public health impact that is not equivocal, and that NASG introduction had a positive population-based effect. Conclusions A successful NASG demonstration took place over the course of 18 months in the existing health system of Northern Province, Zambia, suggesting that incorporation of NASG into the standard of care for obstetric emergency in the Zambia public sector is feasible and can be maintained without external support.